The Role of Vegetation in Controlling Air Temperature Resulting from Urban Heat Island - Siti Badriyah Rushayati; Annisa Dyra Shamila; Lilik Budi Prasetyo (Universitas Muhammadiyah Surakarta, 2018)
Urban Heat Island (UHI) is a phenomenon exhibited by many worldwide cities. Cities, which exhibit UHI, possess higher air temperature as compared with air temperature in the surrounding areas. However, existing UHI profiles are those occurring in subtropical areas which are, of course, very much different from those in tropical cities. Therefore, the objectives of this study are to describe the UHI’s profile and the role of tree vegetation in controlling and reducing air temperature in a tropical region’s urban areas and, particularly, in DKI Jakarta. In this study, we carried out a spatial analysis of land cover and the distribution of air temperature. In this regard, we based our analysis of the potency of tree vegetation in reducing air temperature in UHI’s profile on the distribution of air temperature in various types of land cover which extended from north to south and from east to west. The ranges of air temperature in land cover in the form of built-up areas were 29.2-39.5 ⁰C, non-tree vegetation 28.6-35.6 ⁰C, and tree vegetation 27.0-35.7 ⁰C. Accordingly, tree vegetation has the highest potential to reduce air temperature and to overcome the phenomenon of UHI.